2022
DOI: 10.1002/acr.24730
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Rheumatoid Arthritis and Depressive Symptoms Over Time: Are There Differences by Education, Race/Ethnicity, and Gender?

Abstract: Objective. To examine associations between changes in rheumatoid arthritis (RA) symptoms and depressive symptoms adjusted for other time-varying characteristics, and to test if these associations differed by education, race/ethnicity, or gender.Methods. Data from the 1988-1998 US National Rheumatoid Arthritis Study were analyzed (n = 854). Time-varying covariates included year of the study, pain, functional ability, household work disability, parental status, marital status, employment status, and social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…More women than men develop RA, however this study showed that a higher proportion of men managed to remain employed compared to women [18,36,42,43,46,62,71,89,101,116]. Previous studies have shown inconsistent results in this regard.…”
Section: Key Findingscontrasting
confidence: 53%
See 1 more Smart Citation
“…More women than men develop RA, however this study showed that a higher proportion of men managed to remain employed compared to women [18,36,42,43,46,62,71,89,101,116]. Previous studies have shown inconsistent results in this regard.…”
Section: Key Findingscontrasting
confidence: 53%
“…Higher educational levels were associated with a greater possibility of employment [30,43,45,46,51,62,86]. This is probably due to enhanced job opportunities, flexibility, lower physical workload, better insurance coverage, and improved health care for well-educated individuals.…”
Section: Key Findingsmentioning
confidence: 97%
“…The higher depression scores and low CSFQ scores in our study could add to the lowered well-being amongst female patients shown in some studies [ 27 , 49 ]. However, other studies found no gender difference in the prevalence of depression amongst patients with RA [ 1 , 50 ]. These differences may be due to scale measurement bias and would be worthy of further exploration using a male-specific depression scale that addresses ways through which men traditionally express depression (i.e., anger, aggression, substance abuse, self-sabotage and risk-taking behaviours) [ 51 ].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, there are also gender-related differences in the causes of severity of depression among RA patients. According to McQuillan et al ( 2022 ), RA functional disability is more strongly associated with depression in males than in females. Depressive symptoms in female patients appear to be more closely related to poor sleep quality or family pressure (Hughes et al, 2021 ; Hamasaki et al, 2022 ).…”
Section: What Causes Depression In Ra Patients?mentioning
confidence: 99%